2012
DOI: 10.3109/14015439.2012.664655
|View full text |Cite
|
Sign up to set email alerts
|

Modified vocal function exercises: A case report

Abstract: The modified version can be an option for those patients unable to follow the instructions of vocal function exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Other studies have investigated VFEs with protocol modifications that altered the integrity of the prescribed SOVT posture outlined by Stemple et al (1994) and Roy et al (2001). In a retrospective single-subject case study by Radhakrishnan and Scheidt (2012), a modified form of the VFE programme was implemented in a participant with presbylaryngeus. The first modification involved replacing the prescribed SOVT posture with the vowel/o/ , thereby lessening the degree of semi-occlusion by an unknown amount.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have investigated VFEs with protocol modifications that altered the integrity of the prescribed SOVT posture outlined by Stemple et al (1994) and Roy et al (2001). In a retrospective single-subject case study by Radhakrishnan and Scheidt (2012), a modified form of the VFE programme was implemented in a participant with presbylaryngeus. The first modification involved replacing the prescribed SOVT posture with the vowel/o/ , thereby lessening the degree of semi-occlusion by an unknown amount.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while there is evidence to suggest that VFEs are efficacious in improving the disordered (Berg, Hapner, Klein, & Johns, 2008; Gelfer & Van Dong, 2013; Gillivan-Murphy, Drinnan, O’Dwyer, Ridha, & Carding, 2006; Gorman, Weinrich, Lee, & Stemple, 2008; Jafari et al, 2017; Kaneko et al, 2015; Kapsner-Smith et al, 2015; Kumar, Sharma, Vir, & Panda, 2016; Lim, Kim, Kwon, & Park, 2009; Nguyen & Kenny, 2009; Pasa, Oates, & Dacakis, 2007; Patel, Bless, & Thibeault, 2011; Pedrosa, Pontes, Pontes, Behlau, & Peccin, 2016; Radhakrishnan & Mathisen, 2016; Radhakrishnan & Scheidt, 2012; Roy et al, 2003; Roy et al, 2001; Sauder, Roy, Tanner, Houtz, & Smith, 2010; Sharma, De, Martin, & Pracy, 2009; Tanner, Sauder, Thibeault, Dromey, & Smith, 2010; Tay, Phyland, & Oates, 2012; Teixeira & Behlau, 2015; Ziegler, Verdolini Abbott, Johns, Klein, & Hapner, 2014), normal (Ellis & Beltyukova, 2011; Stemple et al, 1994), and well-trained voice (Guzman, Angulo, Munoz, & Mayerhoff, 2013; Sabol, Lee, & Stemple, 1995), the precise mechanism of physiologic change underlying VFE efficacy remains an open question. Furthermore, it is unclear whether the prescribed SOVT posture is an essential component of VFE efficacy, or whether other vocal tract postures are capable of achieving similar results.…”
Section: Introductionmentioning
confidence: 99%
“…While a total of 27 outcome studies have demonstrated VFEs to be effective in enhancing normal (Ellis & Beltyukova, 2011; Stemple et al, 1994), pathological (Berg, Hapner, Klein, & Johns, 2008; Gelfer & Van Dong, 2013; Gillivan-Murphy, Drinnan, O’Dwyer, Ridha, & Carding, 2006; Gorman, Weinrich, Lee, & Stemple, 2008; Jafari et al, 2017; Kaneko et al, 2015; Kapsner-Smith, Hunter, Kirkham, Cox, & Titze, 2015; Kumar, Sharma, Vir, & Panda, 2016; Lim, Kim, Kwon, & Park, 2009; Nguyen & Kenny, 2009; Pasa, Oates, & Dacakis, 2007; Patel, Pickering, Stemple, & Donohue, 2012; Pedrosa, Pontes, Pontes, Behlau, & Peccin, 2016; Radhakrishnan & Mathisen, 2016; Radhakrishnan & Scheidt, 2012; Roy et al, 2003; Roy et al, 2001; Sauder, Roy, Tanner, Houtz, & Smith, 2010; Sharma, De, Martin, & Pracy, 2009; Tanner, Sauder, Thibeault, Dromey, & Smith, 2010; Tay, Phyland, & Oates, 2012; Teixeira & Behlau, 2015; Ziegler, Verdolini Abbott, Johns, Klein, & Hapner, 2014), and well-trained voices (Guzman, Angulo, Munoz, & Mayerhoff, 2013; Sabol, Lee, & Stemple, 1995), little is known about the ideal dosage, or the dosage that yields the greatest benefit without causing damage (Roy, 2012). According to Stemple et al (1994), the standard protocol for VFE home practice involves performing a set of four exercises, two times each, both morning and evening.…”
Section: Introductionmentioning
confidence: 99%
“…The term exposure is used here in place of dosage since none of these studies explicitly or consistently manipulated dosage; however, the study method in some way changed the recommended amount of intervention or practice provided. Based on these studies, a few inferences were made: a) lower exposure to VFEs may be sufficient to improve the normal voice (Ellis & Beltyukova, 2011); b) lower exposure to VFEs may not improve the normal voice to the same extent that a higher exposure would (Ellis & Beltyukova, 2011); c) lower exposure to VFEs may be insufficient to improve the disordered voice (Pasa et al, 2007); d) traditional exposure to VFEs with modified technique may be sufficient to improve the disordered voice (Radhakrishnan & Scheidt, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo a literatura, após intervenção fonoaudiológica vocal nos casos de presbifonia, foi verificado melhora das características acústicas como, F0, jitter, shimmer, proporção harmônico-ruído e Índice de Fonação Suave (Radhakrishnan;Scheidt, 2012;Lu;Presley;Lammers, 2013;Nemr et al, 2014;Kaneko et al, 2015;Zhu et al, 2018). Embora tenha-se observado essas melhoras, nenhum deles utilizou a técnica de trato vocal semi-ocluído com uso de tubos de ressonância,…”
Section: Análise Auto Percepção Da Vozunclassified